A mobile health intervention in HIV primary care: supporting patients at risk for ART non-adherence. Issue 5 (12th December 2020) - Ventuneac, Ana; Kaplan-Lewis, Emma; Buck, Jessamine; Roy, Randi; Aberg, Caitlin E.; Duah, Bianca A.; Forcht, Emily; Cespedes, Michelle; Aberg, Judith A.
Abstract : Mobile health (mHealth) interventions that are integrated in HIV clinical settings to facilitate ongoing patient-provider communication between primary care visits are garnering evidence for their potential in improving HIV outcomes. Rango is an mHealth intervention to support engagement in HIV care and treatment adherence. This study used a single-arm prospective design with baseline and 6-month assessments for pre-post comparisons, as well as a matched patient sample for between-group comparisons to test Rango's preliminary efficacy in increasing viral suppression. The Rango sample (n = 406) was predominantly 50 years of age or older (63%; M = 50.67; SD = 10.97, 23–82), Black/African-American (44%) or Hispanic/Latinx (38%), and male (59%). At baseline, 18% reported missing at least one dose of ART in the prior three days and chart reviews of recent VL showed that nearly 82% of participants were virally suppressed. Overall 95% of the patients enrolled in Rango returned for a medical follow-up visit. Of the 65 unsuppressed patients at baseline who returned for a medical visit, 38 (59%) achieved viral suppression and only 5% of the suppressed group at baseline had an increase in viral load at 6 months despite being at risk for ART non-adherence. While viral suppression was similar between Rango participants and patients receiving treatment as usual over the same time period, it is unknown whether those patients were similarly at risk for non-adherence. Our findings support efforts to formally test this innovative approach in addressing ART non-adherence and viral suppression particularly to reach HIV treatment goals.